Impact of Competitive Strategy on Corporate Governance in Companies Listed on Vietnam’s Stock Market - Thoan, Le Thi; Thuy, Vo Thi Ngoc; Long, Tran Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 3, 2022)
In this study, we explores the relationship between competative strategy and corporate governance through the analysis of 562 non-financial companies listed on the Vietnam’s stock market in 2010-2019, thereby making judgments about competitive strategies to determine which strategy has a meaningful impact on corporate governance. It is found that a cost leadership strategy has a negative impact on corporate governance, and a differentiation strategy has a positive impact on corporate governance. In addition, our study provides evidence for further studies in this field and suggests some possible solutions for investors and regulators in Vietnam.